Numerical investigation of vortex-induced vibrations of a flexible riser with staggered buoyancy elements - Wu, J. (MDPI AG, 2020)
This paper presents a numerical algorithm used together with a Finite-Element based Vortex-Induced Vibration (VIV) prediction software VIVANA to obtain a hydrodynamic force coefficient database based on response measurements of flexible riser VIV model test of staggered buoyancy elements. The excitation coefficient database is parameterized; and the representative parameters are systematically varied in VIVANA simulations until the predicted responses in terms of mode number, response frequency, root-mean-square (RMS) response amplitude, and RMS curvature agree well with the experimental data under same flow and boundary conditions. An optimal set of force coefficient database for both the buoyancy element and the bare riser section is obtained and a significant improvement in VIV prediction by VIVANA is achieved. The obtained hydrodynamic force coefficient database can be also applied to other empirical VIV prediction programs. The sensitivity of using the same database to predict the VIV of different configurations has also been investigated. Â© 2020 by the authors.